DETECTION OF THE MOST IMPORTANT PATHOGENIC BACTERIA AFFECT EXTERNAL ORGANS OF CYPRINUS CARPIO IN WASIT PROVINCE - Garabawi, Ali J.; Al-Faragi, Jamal K.; Zakair, Khalied Y. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was aimed to find the most common causative agents relates to skin ulceration in most common fish farming (ponds and cages) affects Cyprinus carpio in Wasit province harvested from three different regions. The laboratory isolation and detection of bacteria in this study was carried out in medical laboratory techniques in Middle Technical University and Central Public Health Laboratory in Baghdad from September to December 2020. For this study 240 infected common carp Cyprinus carpio L. were used, 120 samples from cages and 120 samples from ponds. Samples were taken from three regions, which represented the north, central, and south of the governorate. Samples from skin ulcers were taken from affected areas in the body of the fish, skin, gills and fins, then transporting to the laboratory to perform bacterial culture. The present study illustrates that the common causative agent of ulceration in fish skin, gills and fins was bacteria with most detected bacteria were Aeromonas hydrophila (56.7%) in cages and (37.5%) in ponds, followed by Pseudomonas aeruginosa (40.83%) in cages and (35.08%) in ponds, and Citrobacter freundii (41.66%) in cages and (25.8%) in ponds through the months including in this study. In conclusion, the most important pathogenic bacteria related to skin ulceration in both cages and ponds in all three locations in Wasit province were Aeromonas hydrophila, Pseudomonas aeruginosa and Citrobacter freundii. The infection rate was higher in cages compared to ponds because of increase pollution by sewage and organic compound and due to stress condition resulting from higher stoking density.